Haemoconcentration in Yankasa sheep exposed to prolonged water deprivation - Igbokwe, I.O. (Elsevier, 1993)
Five non-pregnant, healthy Yankasa ewes were deprived of water for 10 d with only one watering period during hot dry weather. On d 5, the mean body weight significantly (P0.05). Sheep were watered on an ad libitum basis for only 12 h after sample collection on d 5. On d 10, the mean body weight was only slightly decreased (P